Effect of Cinnamon on Distribution and Number of Mast Cells in Diabetic Rat Liver - Ertuğrul, Tuğrul; Ertugrul, Nazife Ulker (My University, 2022)
ABS TRACT Objective: In the present study, we investigated the effects of cinnamon on distribution and number of mast cells (MCs) in liver tissue of diabetic rats. Material and Methods: The rats used as the control group received no application. All rats in the diabetes and diabetes+cinnamon groups were made diabetic by a single dose intraperitoneal injection of streptozotocin. In our study, after establishment of diabetes, cinnamon extract was administered daily by oral gavage for 14 days to both cinnamon and diabetes+cinnamon groups. To determine the MCs, the tissue sections were stained both with toluidin blue (TB) and Alcian blue/Safranin O (AB/SO) methods. Results: It was determined that the number of MCs in the portal areas increased with diabetes. As a notable finding, it was observed in our study that cinnamon reduced the MC numerical increase that increases with diabetes in the diabetes+cinnamon group. As a result of the AB/SO combined staining method application, it was shown that there were 3 types of MC populations as blue AB(+), red SO(+) and mixed color AB/SO(+) in rat liver tissue. It was found that cinnamon application was effective on the SO(+) content in diabetes. Conclusion: In conclusion, the findings of this study show that diabetes alters the number of MC and cinnamon can reduced the increase in diabetesrelated MC numbers. In addition, this study demonstrated the possible effects of diabetes and cinnamon on the histochemical and morphological differences of MCs in rat liver.
Keywords: Biyoloji; Tıbbi Araştırmalar Deneysel; Patoloji; Mikrobiyoloji; Genetik ve Kalıtım; Veterinerlik; Zooloji